2017
DOI: 10.15388/klbt.2017.11181
|View full text |Cite
|
Sign up to set email alerts
|

A corpus-driven analysis of structural types of lexical bundles in court judgments in English and their translation into Lithuanian

Abstract: Formulaicity is one of the characteristic features of legal discourse, which manifests itself not only at the level of wording, "but also in the content, structure and layout"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The grammatical the organization of formulaic sequences forms the base for the structural classification. Depending on whether they contain nouns, prepositional phrases, verbs, or clause fragments, lexical bundles are classified as follows: (1) grammatical groups which contain word or phrase fragments (also known as "nominal lexical bundles" or "prepositional lexical bundles"); (2) lexical bundles that contain verb phrase fragments (also known as "verbal lexical bundles"); and (3) word or phrase fragments contain sentence sequences [7]. The basis for methodically examining lexical bundles from a is laid out by Bieber et al's structural its classification of lexical categories, In a classic analysis of the lexical bundle, it found that phrases have significant connections with one another various sentence structure, or idiomatic expressions structures, and 12 classes of lexical groups in academic discourse were identified [11].…”
Section: Structure Lexical Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The grammatical the organization of formulaic sequences forms the base for the structural classification. Depending on whether they contain nouns, prepositional phrases, verbs, or clause fragments, lexical bundles are classified as follows: (1) grammatical groups which contain word or phrase fragments (also known as "nominal lexical bundles" or "prepositional lexical bundles"); (2) lexical bundles that contain verb phrase fragments (also known as "verbal lexical bundles"); and (3) word or phrase fragments contain sentence sequences [7]. The basis for methodically examining lexical bundles from a is laid out by Bieber et al's structural its classification of lexical categories, In a classic analysis of the lexical bundle, it found that phrases have significant connections with one another various sentence structure, or idiomatic expressions structures, and 12 classes of lexical groups in academic discourse were identified [11].…”
Section: Structure Lexical Bundlesmentioning
confidence: 99%
“…Lexical Bundles are a type of multiword unit, and 'phraseology' and 'formulaic sequences/language' are two words used to describe them [6]. Lexical bundles will be among the main types of formulaic linguistic constructions, and they have recently attracted the attention of numerous scholars who have realized how prevalent they are in both spoken and written language [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of these formulaic structures in linguistics has been studied as so-called lexical bundles [13], such as 'on the other hand', 'as can be seen' or 'it is recommended that'. Researchers focus predominantly on more or less specialized discourses: academic discourse [14], medical leaflets [15] and legal texts, the latter from perspectives such as genre [16], linguistic structure [6], translation strategies [17] or legal semantics [18].…”
Section: The Study Of Lexical Bundles and The Research Aimmentioning
confidence: 99%
“…Lexical bundles and other formulaic sequences are considered to be the building blocks of a given discourse ( [20], [6]) which improve processing efficiency in communication [21]. One's command of such multi-word sequences is also said to have a sociological value for signalling an individual's belonging to a community [12] or a pedagogical value in teaching and mastering of specialized discourses [22].…”
Section: The Study Of Lexical Bundles and The Research Aimmentioning
confidence: 99%
“…Simpson-Vlach & Ellis 2010; Martinez & Schmitt 2012;Salazar 2014). One may also note the scarcity of cross-linguistic studies focusing on recurrent n-grams or LBs, with the notable exceptions of Forchini and Murphy (2008), Granger (2014), Oksefjell Ebeling and Ebeling (2016), Biel (2017), Berūkštienė (2017), Grabowski (2018a) or Grabar and Lefer (2015). Approaching those peculiar MWUs from the perspective of translation, the last-mentioned study is targeted at identification of LBs in English and French EU parliamentary debates in order to develop bilingual lexicons to be further used in computer-assisted translation tools or machine translation tools.…”
Section: Recurrent Multi Word Sequences As a Problem In Translationmentioning
confidence: 99%